EVALUACIÓN PRESUPUESTARIA AL GOBIERNO AUTÓNOMO DESCENTRALIZADO PARROQUIAL RURAL DE CUMBARATZA DEL CANTÓN ZAMORA, PROVINCIA DE ZAMORA CHINCHIPE, PERÍODO 2014 - Criollo Juncay, Paquita Silvana (2016)
The thesis called, "BUDGETARY EVALUATION TO THE AUTONOMOUS DECENTRALIZED PAROCHIAL RURAL GOVERNMENT OF CUMBARATZA OF THE CANTON ZAMORA, PROVINCE OF ZAMORA CHINCHIPE, PERIOD 2014 ", executed as prerequisite to choosing the degree and Engineer's title in Accounting and Audit, Public Book-keeper Auditor. To expire with the aim of the thesis, firstly an interview was realized to the President and treasurer of the entity, with the purpose of determining the importance of the topic in study and of observing the fulfillment of the legal dispositions, applied in the budgetary process. Then one proceeded to extract the physical documentation as: operative annual plan, initial budget been of budgetary execution, budgetary bonds of expenses and income and the general report for programmatical axes, to have a better perception of the behavior of each one of the budget items; in addition the summary of the bibliographical material is based on the budgetary regulation, laws, codes and regulations issued by the Department of Finance. To determine the degree of fulfillment of the goals and aims reached in the institution one proceeded to apply budgetary indicators in order to determine the efficiency and efficiency in the managing of the assigned resources; then a comparison was effected between the operative annual plan and the general report by programmatical axes, to determine if there were executed all the activities programmed of agreement to the assigned budget; and finally the report was elaborated to the executives of the entity, in which there consist the respective conclusions and 5 recommendations that it will be of great help for the correct capture of decisions and to improve the management in fulfillment with the pertinent dispositions in later activities. The application of indicators during the period 2014, demonstrates that the institution had a degree of fulfillment of 90,74 % and a diversion of 9,26 % of the total of codified income, this diversion corresponds to the group of income of the capital and of financing, same that were not collected in its entirety to expire with the planned activities. Of equal way the total of codified expenses show a degree of I complete of 96.03 % and a diversion of 3,97 %, which has not been executed due to little management of the collection, for such a reason in the State of Budgetary Execution demonstrates a budget deficit due to the fact that the expenses are major that the income, of equal way the results presented in the report of account surrender, differs from the royal behavior of the budget in budgetary bonds. The materials and methods applied in the present work of thesis described in his pertinent part contributed to the development and fulfillment of the raised aims, beginning for the theory and development of the practice, and he concludes with a report, product of the results obtained of the budgetary evaluation.